Adapting and implementing Acceptance and Commitment Therapy groups to support personal recovery of adults living with psychosis: a qualitative study of facilitators' experiences. Issue 4 (2nd October 2022) - Gates, Jesse; Goldstone, Eliot; Clemente, Jacinta; Cugnetto, Marilyn; Morris, Eric M.J.; Farhall, John
ABSTRACT: Background: : Psychosocial, evidence-based interventions (EBI) may support personal recovery from psychosis; however, little is known about their implementation. Methods: : This paper describes the adaptation, implementation, and evaluation of a psychosocial EBI, group Acceptance and Commitment Therapy (ACT), designed to support personal recovery of people living with psychosis who are accessing Australian public mental health services. We outline the process of adapting and implementing a group program, and present results of a qualitative analysis of facilitator experiences of the first 6 groups conducted involving 69 participants. Eight facilitators participated in an expert-led reflective interview developed to gather feedback in five domains. Results: : A thematic analysis of transcribed audio-recorded interviews elicited nine themes that indicated: local adaptations facilitated participant learning; targeted efforts to engage all stakeholders were successful; clinical supervision and research support by local experts enabled program implementation and evaluation; implementation offered facilitators personal rewards; and a need for further engagement of organisational support. Discussion: : This paper identifies enablers of successful adaptation and implementation of ACT groups for recovery from psychosis, an EBI in public mental health services. Study limitations include the risk of a self-serving reporting bias and the absence of lived experience expertise in group facilitation and evaluation.